Efficacy of intravitreal injection of Ziv-aflibercept before vitrectomy for proliferative diabetic retinopathy - Amin E. Nawar; Ahmed R. Alagorie (Delta Journal of Ophthalmology)
Purpose The aim of this study was to evaluate the efficacy of intravitreal injection of Ziv-aflibercept before small-gauge pars plana vitrectomy compared to pars plana vitrectomy alone in eyes with advanced diabetic eye disease.